Factors Affecting the Public Opinion of Advertisements with respect to Apparels - Ubeja, S; Acharya, S; Jain, P; Loya, A; Tiwari, R (International Journal of Computer Sciences and Engineering, 2025)
In the present time of data blast and the universe of media, promotions assume a noteworthy part in changing the conduct and state of mind of shoppers towards the items appeared in the commercials. The promotions not just change the method for item is devoured by client however modify the state of mind with which they take a gander at the item. Everywhere throughout the world, ads have been utilized since ages for a wide assortment of brands. For in the course of the most recent two decades, a sharp increment in notices per brand has been seen. Ads have awesome impact in buying choice of clients for specific brands. The present study investigates various factors that affect the public opinion of advertisements especially for apparels. The study is also to assess the influence of demographic factors on the public opinion of advertisement towards apparels. By taping more than 200 responses we analyzed the data using ANOVA and T-test to get the valid output through SPSS package. Thus this research will benefit organizations in creating better ads keeping in mind the factors that stimulate people to buy the product after watching advertisements and how they can do more publicity. Also it will help the firms in effective planning of promotional mix and take further advertisement related decisions.